Dynamic Impacts of Sustainable Energies, Technological Innovation, Economic Growth, and Financial Globalization on Load Capacity Factor in the Top Nuclear Energy-Consuming Countries - Islam, Samanta; Raihan, Asif; Paul, Arindrajit; Ridwan, Mohammad; Rahman, Md. Shoaibur; Rahman, Junaid; Tanchangya, Tipon; Bibi, Robeena; Sumaira; Jubayed, Abdullah Al (Journal of Environmental and Energy Economics, 2024)
Nuclear energy is often regarded as a very efficient method for promoting environmental sustainability. This study seeks to investigate the influence of nuclear energy, renewable energy, financial globalization, technical innovation, and economic expansion on the sustainability of the environment in the top 10 economies that consume nuclear energy. The research analyzed data from 1990 to 2020. The load capacity factor (LCF) serves as a novel indicator for ecological sustainability, elucidating the impact of human activities on ecological sustainability and the mechanisms by which nature mitigates human-induced harm. This study employed the Panel Dynamic Ordinary Least Squares (DOLS) method to analyze the dynamic effects of the variables being studied. The estimation results suggest that the use of nuclear and renewable energy, as well as financial globalization, contribute to environmental sustainability by raising the LCF. On the other hand, economic expansion and technological innovation negatively impact ecological sustainability as it decreases the LCF. The study suggests that the governments of the top 10 nations with the highest nuclear energy consumption should actively promote increased investment in green technology and renewable energy sources in order to attain environmental sustainability.